Chip-based monolithic microextraction combined with ICP-MS for the determination of bismuth in HepG2 cells. Issue 7 (9th May 2016) - Zhang, Jing; Chen, Beibei; Wang, Han; Huang, Xi; He, Man; Hu, Bin
Abstract : Chip-based monolithic microextraction combined with ICP-MS provides a new strategy for the analysis of trace metals in cells. Abstract : Microfluidic devices provide a potential platform that can specialize in miniaturization, integration and automation. In this study, we prepared ethanediamine modified poly glycidyl methacrylate trimethylol propane triacrylate monolithic columns (poly (GMA- co -TRIM-NH2 )) in a microfluidic chip channel and established a novel method by combining chip-based poly (GMA- co -TRIM-NH2 ) monolithic microextraction with inductively coupled plasma mass spectrometry (ICP-MS) for the determination of bismuth in cell samples. Various factors affecting chip-based monolithic microextraction of bismuth were investigated. Under the optimized conditions, the limit of detection was 0.21 ng mL −1 and the relative standard deviation for bismuth was 6.0% ( c = 5 ng mL −1, n = 7). The method was successfully applied to the analysis of HepG2 cells incubated with bismuth. With consumption of ∼600 cells, the average amount of bismuth was determined to be at the sub picogram level in a single cell. The prepared chip-based poly (GMA- co -TRIM-NH2 ) monolithic column had a high-surface area and exhibited high extraction efficiency towards bismuth. The proposed chip-based monolithic microextraction method combined with ICP-MS provides a novel strategy for the analysis of trace metals in cells.